Accuracy in Archery Shooting is linked to the Amplitude of the ERP N1 to the Snap of Clicker - Hayri Ertan; Suha Yagcioglu; Alpaslan Yılmaz; Pekcan Ungan; Feza Korkusuz (Montenegrin Sports Academy, 2021)
An archer requires a well-balanced and highly reproducible release of the bowstring to attain high scores in competition. Recurve archers use a mechanical device called the "clicker" to check the draw length. The fall of the clicker that generates an auditory stimulus should evoke a response in the brain. The purpose of this study is to evaluate the event-related potentials during archery shooting as a response to the fall of the clicker. Fifteen high-level archers participated. An electro cap was placed on the archers' scalps, and continuous EEG activity was recorded (digitized at 1000 Hz) and stored for off-line analysis. The EEG data were epoched beginning 200 ms before and lasting 800 ms after stimulus marker signals. An operational definition has been developed for classifying hits corresponding to hit and/or miss areas. The hit area enlarged gradually starting from the centre of the target (yellow: 10) to blue (6 score) by creating ten hit area indexes. It is found that the snap of the clicker during archery shooting evokes N1-P2 components of long-latency evoked brain potentials. N1 amplitudes are significantly higher in hit area than that of miss areas for the 2nd and 4th indexes with 95% confidence intervals and 90% confidence intervals for the 1st and 3rd indexes with 90% confidence intervals. We conclude that the fall of the clicker in archery shooting elicits an N1 response with higher amplitude. Although evoked potential amplitudes were higher in successful shots, their latencies were not significantly different from the unsuccessful ones.